(untitled) (Research, Society and Development, 2022)
This article reports the experience of an intervention project designed to teach web information search strategies, in order to allow students to better satisfy their information needs. This intervention was divided into three phases: diagnosis of the search strategies used by the students; teaching Web information search strategies and indicating information sources for academic activities; evaluation of what the students learned by attending the course. At the end of the intervention, the students reported optimism regarding the advanced search tools on Google learned and envisioned more assertive and direct queries, causing them to spend less time with the disposal of useless results resulting from inaccurate and generalist queries. With regard to scientific journals, students eulogized the advantage of easy access to reliable scientific articles, which, in addition to offering quality content, eliminate the need to investigate the reliability of the content. With regard to Pergamum, the students highlighted the possibility of searching for titles without having to be present at the institution, in addition to the greater possibility of knowledge of the campus collection and other network campuses, in case of eventual future need. Finally, it is concluded that the more experience the students acquire with the search and use of information, the better their learning of school content may be and the better prepared they will be for the challenges life presents them.